The balance between photosynthesis and respiration explains the niche differentiation between Crocosphaera and Cyanothece - Masuda, Takako; Inomura, Keisuke; Gao, Meng; Armin, Gabrielle; Kotabová, Eva; Bernát, Gábor; Lawrenz-Kendrick, Evelyn; Lukeš, Martin; Bečková, Martina; Steinbach, Gábor; Komenda, Josef; Prášil, Ondřej (Computational and structural biotechnology journal, 2023)
Crocosphaera and Cyanothece are both unicellular, nitrogen-fixing cyanobacteria that prefer different environments. Whereas Crocosphaera mainly lives in nutrient-deplete, open oceans, Cyanothece is more common in coastal, nutrient-rich regions. Despite their physiological similarities, the factors separating their niches remain elusive. Here we performed physiological experiments on clone cultures and expand upon a simple ecological model to show that their different niches can be sufficiently explained by the observed differences in their photosynthetic capacities and rates of carbon (C) consumption. Our experiments revealed that Cyanothece has overall higher photosynthesis and respiration rates than Crocosphaera. A simple growth model of these microorganisms suggests that C storage and consumption are previously under-appreciated factors when evaluating the occupation of niches by different marine nitrogen fixers.
Keywords: UCYN-C; Niche separation; UCYN-B; Carbon consumption